Cardiovascular Complications in a Patient with Marfan Syndrome and Mitral Valve Prolapse. Systematic literature review. - Cruz-Ossa, Natalia (2022)
Background: Marfan syndrome (MS) is a disorder that affects connective tissue and is associated with abnormalities of the musculoskeletal system. Among the complications that can be triggered by MS, cardiovascular anomalies that lead to unfavorable outcomes such as mitral valve prolapse (MVP) must be taken into account. MVP in patients with MS can trigger subsequent complications, such as mitral regurgitation and heart failure. Objective: Identify the cardiovascular complications of a patient with Marfan syndrome and mitral valve prolapse. Materials and methods: Systematized search of the literature in Medline, through PubMed, using the guidelines of the PRISMA Declaration for the selection of published studies. Results: Based on the 17 publications obtained in the systematized literature search process, the cardiovascular complications described were mitral regurgitation, mitral valve dysfunction, mitral valve replacement, infective endocarditis, dilatation of cavities and large vessels, heart failure, aortic dissection, reduced life expectancy, death, among others. Conclusions: MVP in patients with MS is one of the most important cardiovascular anomalies that lead to various cardiovascular complications, the main ones being mitral regurgitation and heart failure. For this reason, it is essential to recognize this relationship in order to prevent their development in time.